Recurrent translocation t(10;17)(p15;q21) in minimally differentiated acute myeloid leukemia results in ZMYND11/MBTD1 fusion. Issue 3 (26th November 2015) - de Rooij, Jasmijn D.E.; van den Heuvel‐Eibrink, Marry M.; Kollen, Wouter J.W.; Sonneveld, Edwin; Kaspers, Gertjan J.L.; Beverloo, H. Berna; Fornerod, Maarten; Pieters, Rob; Zwaan, C. Michel
Abstract : Pediatric acute myeloid leukemia (AML) is a heterogeneous disease, characterized by different collaborating karyotypic and molecular abnormalities, which are used in risk group stratification. In ∼20% of the pediatric AML cases a specific genetic aberration is still unknown. Minimally differentiated myeloid leukemia or FAB‐type M0 is a rare morphological subtype of AML. The translocation t(10;17)(p15;q21) is described to be recurrent in minimally differentiated AML, but the involved genes and location of the breakpoints have so far not been identified. In this study, we show that this translocation results in an in‐frame translocation fusing exon 12 of the tumor suppressor gene ZMYND11 to exon 3 of the chromatin protein MBTD1, encoding a protein of 1, 054 amino acids, while the reciprocal fusion product is predicted to lack a productive start codon. Gene expression profiling of the leukemic cells showed high HOXA expression. ZMYND11, also known as BS69, is a tumor suppressor that specifically recognizes H3K36me3, which is linked to aberrant HOXA expression in leukemogenesis. Aberrant expression of the genes involved in this fusion may thus contribute to the HOXA‐ phenotype observed with gene expression profiling. © 2015 Wiley Periodicals, Inc.